Exploring the Virulence Factors of Campylobacter jejuni Targeted by Quercetin: A Bioinformatics Approach - Sintice Dhea Valerie; Nawan Nawan; Ysrafil Ysrafil (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Campylobacter jejuni is a major cause of bacterial gastroenteritis and continues to develop resistance to commonly used antibiotics, especially fluoroquinolones, creating a need for alternative therapeutic approaches. Quercetin, a natural flavonoid, exhibits antibacterial activity by disrupting membrane stability, inhibiting nucleic acid synthesis, and reducing virulence factor expression. This study aimed to predict the interaction between quercetin and essential proteins of Campylobacter jejuni and to identify virulence-associated proteins with immunogenic potential using a bioinformatics approach. The protein–compound interaction analysis was performed using STITCH, while virulence functions were predicted using VirulentPred and VICMPred. B cell and T cell epitope predictions were conducted using the IEDB Analysis Resources, and antigenicity was evaluated using VaxiJen. The results showed that quercetin interacts with key proteins such as ATP synthase, DnaK, catalase, and oxidoreductase, which contribute to bacterial survival through energy metabolism and oxidative stress regulation. Five virulence-associated proteins were identified with strong antigenicity and immunogenic potential, with most predicted to be located on the cytoplasmic membrane. These findings suggest that quercetin may function as a multi-target antimicrobial agent that interferes with essential cellular processes while promoting immune recognition, supporting its potential as a candidate for future therapeutic development against antibiotic-resistant Campylobacter jejuni infections.